2021
DOI: 10.31436/iiumej.v22i2.1747
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties, Water Absorption, and Failure Analyses of Kenaf Fiber Reinforced Epoxy Matrix Composites

Abstract: The potential of natural fibers as one of the candidate materials in the production of fiber-reinforced polymer composites have been widely investigated. In the current study, natural fiber-reinforced polymer composite was fabricated by employing woven kenaf fiber as a reinforcing agent with epoxy resin that acts as a matrix constituent. This composite sample was fabricated using the application of the vacuum infusion method in which the content of kenaf fibers was varied from 30 vol.%, 40 vol.%, and 50 vol.%.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…A review study done by Akil et al, [4] concluded that most kenaf fibre reinforced composites had water absorption up to 25% in distilled water after immersion for 80 hours. Another study done by Yusuff et al, [20] found that as the kenaf fibre loading in kenaf/epoxy composite increases from 30, 40 and 50 vol.%, the water absorption in 5 days is 25%, 28% and 43% respectively. The value of water absorption in kenaf/acrylic based polyester with 45% volume fraction fibre showed 40% for alkali treated and 55% for untreated kenaf fibre [21].…”
Section: Water Absorptionmentioning
confidence: 93%
“…A review study done by Akil et al, [4] concluded that most kenaf fibre reinforced composites had water absorption up to 25% in distilled water after immersion for 80 hours. Another study done by Yusuff et al, [20] found that as the kenaf fibre loading in kenaf/epoxy composite increases from 30, 40 and 50 vol.%, the water absorption in 5 days is 25%, 28% and 43% respectively. The value of water absorption in kenaf/acrylic based polyester with 45% volume fraction fibre showed 40% for alkali treated and 55% for untreated kenaf fibre [21].…”
Section: Water Absorptionmentioning
confidence: 93%
“…The introduction of this kind of natural fibre-based composite in industries could provide manufacturers with a new alternative to generate economical green products with equivalent mechanical strength. Indirectly, the usage of natural fibre-based fibre could help reduce negative environmental impacts, such as air pollution, compared to synthetic fibre [3]. In this study, kenaf is used as the natural fibre and it is a native plant in tropical and subtropical Africa and Asia.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few years, different studies have been undertaken on applications of KF in cementitious materials to investigate the several variables that can play a role and have an impact on the properties and performance of Kenaf Fiber Reinforced Concrete (KFRC), both positively and negatively [30][31][32][33][34][35], however, no specific approaches or clear outlines in place for researchers and practitioners have been devised to improve their chances of developing a large-scale structural application and fully exploiting the properties of KFRC. Academics, in contrast, are progressively employing scientometric analysis to discover new subjective issues in past research [36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%